Human Response to Flood Disaster in Kandawalai in Kilinochchi District in Sri Lanka - Y. Yushanthi; K.W.G. Rekha Nianthi (TDMRC, Universitas Syiah Kuala, 2021)
The flood is one of the extreme weather events in the world. In Sri Lanka, it is a major natural disaster that mainly occurs in the South-West and the North-East monsoon seasons. The human response strategies are explained in the concepts of the disaster management cycle in the PRE and POST stages. People do not satisfactorily respond during these stages in the study area. There have been no systematic studies conducted on how people responded before, during, and after the floods in Kandawalai. The main objective of this study was to examine human responses to PRE flood situations (mitigation and preparedness). This study selected three GN divisions. Questionnaires, surveys, and interviews were carried out to collect primary data and information. The data was analyzed using both quantitative and qualitative methods. Some preparedness and mitigation were undertaken by the Disaster Management Centre (DMC) in Kilinochchi during the PRE flood stage. To reduce floods, the community has used very simple community-based mitigation measures. Only 43% of them took part in flood-awareness programs that taught them how to evacuate from flood-prone areas and how to respond to early warning systems.57% of respondents mentioned that the flood impact could be reduced through better structural mitigation strategies. 10% of the respondents recommended controlling the illegal activities of sewage disposal and soil mining in the Kanakarayan River. The PRE-flood activities should be considered by relevant stakeholders together with community participation, but the government has the main responsibility for mitigating the impacts of the floods in this particular area.